2016
DOI: 10.1001/jamapsychiatry.2015.3058
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Manifestation of Genetic Risk for Schizophrenia During Adolescence in the General Population

Abstract: Importance Schizophrenia is a highly heritable, polygenic condition characterized by a relatively diverse phenotype and frequent comorbid conditions, such as anxiety and depression. At present, limited evidence explains how genetic risk for schizophrenia is manifest in the general population. Objective To investigate the extent to which genetic risk for schizophrenia is associated with different phenotypes during adolescence in a population-based birth cohort. Design, Setting, and Participants This cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
236
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 215 publications
(274 citation statements)
references
References 47 publications
(53 reference statements)
32
236
6
Order By: Relevance
“…57 The PRS-SCZ accounts for about 9% of variance in caseness in studies of psychotic patients and controls. 59 Interestingly, it has been associated with neurodevelopmental problems and/or negative symptoms in several studies of non-ill children, 60 adolescents, 61 and adults. 62 In the huge UK Biobank sample, the PRS-SCZ predicts lower performance on a variety of cognitive tests.…”
Section: Geneticsmentioning
confidence: 99%
“…57 The PRS-SCZ accounts for about 9% of variance in caseness in studies of psychotic patients and controls. 59 Interestingly, it has been associated with neurodevelopmental problems and/or negative symptoms in several studies of non-ill children, 60 adolescents, 61 and adults. 62 In the huge UK Biobank sample, the PRS-SCZ predicts lower performance on a variety of cognitive tests.…”
Section: Geneticsmentioning
confidence: 99%
“…For example, Jones et al [43] recently noted that genetic risk for schizophrenia in adolescence is often expressed as anxiety and negative symptoms. These researchers called for a greater focus on these emotional processes rather than psychotic experiences as candidate disease endophenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, individuals with common mental disorder are more likely to have psychotic experiences than their counterparts with no psychiatric disorder 4 , and such experiences in mood and anxiety disorders predict more severe illness course 4 .…”
Section: Psychotic Experiences and Their Significancementioning
confidence: 99%
“…Therefore, while van Os and Reininghaus argue that individuals in the community with psychotic experiences are more likely to develop a mood or anxiety disorder than a psychotic disorder, these phenomena actually predict psychotic disorders far more strongly 5 . This is because mood and anxiety disorders are much more common than psychotic disorders and frequently occur in the absence of psychotic experiences 4 . Consistent with this, as van Os and Reininghaus note, evidence from a Danish birth cohort study showed that psychotic experiences at age 11-12 years were strongly associated with a family history of psychotic disorder, but not of common mental disorder.…”
Section: Psychotic Experiences and Their Significancementioning
confidence: 99%
See 1 more Smart Citation